Aluminum component and method for manufacturing the same

By forming an anodized coating with an amorphous and crystalline layer on the surface of the aluminum or aluminum alloy base material, the problem of difficulty in increasing the thickness of the anodized coating film and poor insulation in the prior art is solved, and excellent insulation, corrosion resistance and wear resistance of aluminum components are achieved.

CN115917054BActive Publication Date: 2025-04-11HOKKAIDO UNIVERSITY +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180047513.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-09
Filing Date
2021-06-11
Publication Date
2025-04-11
Estimated Expiration
2041-06-11

AI Technical Summary

Technical Problem

The barrier-type anodized coating in the prior art is difficult to increase the thickness, resulting in insufficient wear resistance and hardness, while the plasma electrolytic oxidized coating has the problem of poor insulation.

Method used

Anodized the aluminum or aluminum alloy base material in an electrolyte containing boron atoms with a pH of 7.0 or more and 12.0 or less, an anodized coating film containing an amorphous layer of amorphous aluminum oxide and a crystalline layer of a crystalline aluminum oxide is formed.

Benefits of technology

The anodized coating has excellent insulation, corrosion resistance and wear resistance, and solves the problem of insufficient single performance in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115917054B_ABST
    Figure CN115917054B_ABST
Patent Text Reader

Abstract

An aluminum component (1) comprises a base material (2) comprising aluminum or an aluminum alloy and an anodic oxide film (3) formed on the surface of the base material (2). The anodic oxide film (3) comprises an amorphous layer (31) comprising amorphous aluminum oxide and formed on the base material (2) and a crystalline layer (32) comprising crystalline aluminum oxide and formed on the amorphous layer (31). The base material (2) is subjected to an anodic oxidation treatment in an electrolyte solution containing boron atoms and having a pH of 7.0 to 12.0, thereby forming the anodic oxide film (3) on the base material (2), thereby obtaining the aluminum component (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an aluminum component and a method for manufacturing the same. Background Art

[0002] Aluminum parts have various uses such as building materials, housings of electronic devices, and machine parts. In order to impart characteristics such as designability, corrosion resistance, wear resistance, and insulation, a functional coating may be provided on the surface of an aluminum part.

[0003] As a functional coating provided on the surface of an aluminum component, an anodic oxide coating is known. The characteristics of the anodic oxide coating vary depending on the structure and manufacturing method of the anodic oxide coating. For example, Patent Document 1 describes a method for forming an anodic oxide aluminum film, characterized in that a substrate with aluminum exposed on the surface is immersed in a first electrolyte to perform anodization of the aluminum, and then the substrate is immersed in a second electrolyte to further perform anodization, wherein the first electrolyte dissolves a boron-containing electrolyte, and the second electrolyte dissolves a boron-free electrolyte.

[0004] In addition, Patent Document 2 describes a method for forming a ceramic coating, which is characterized in that a ceramic coating containing aluminum oxide is formed on the surface of an aluminum or aluminum alloy substrate by anodic spark discharge in an aqueous electrolytic bath containing (a) cations containing nitrogen atoms and (b) aminocarboxylate anions whose stability constant relative to aluminum is greater than 9.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 10-107027

[0008] Patent Document 2: Japanese Patent Application Publication No. 2003-171794 Summary of the invention

[0009] Problems to be solved by the invention

[0010] According to the method of Patent Document 1, an anodic oxide film called a barrier type anodic oxide film can be formed. The barrier type anodic oxide film is relatively dense, so it has excellent insulation and corrosion resistance. However, it is difficult to increase the thickness of the barrier type anodic oxide film, so there are problems such as poor wear resistance and hardness.

[0011] In addition, according to the method of Patent Document 2, an anodic oxide film called a plasma electrolytic oxide film can be formed. The plasma electrolytic oxide film contains crystalline aluminum oxide and can be easily increased in thickness, so it has excellent wear resistance. However, the plasma electrolytic oxide film is prone to form pores, so there is a problem of poor insulation.

[0012] The present invention has been made in view of the above background, and an object of the present invention is to provide an aluminum component having an anodized film excellent in insulation, corrosion resistance, and wear resistance, and a method for producing the same.

[0013] Solutions to Solve Problems

[0014] One embodiment of the present invention is an aluminum component, which has a base material including aluminum or an aluminum alloy and an anodized coating formed on the surface of the base material, wherein the anodized coating has an amorphous layer including amorphous aluminum oxide and formed on the base material, and a crystalline layer including crystalline aluminum oxide and formed on the amorphous layer.

[0015] Another aspect of the present invention is a method for producing an aluminum part, which is the method for producing an aluminum part of the above aspect, wherein the base material is anodized in an electrolyte containing boron atoms and having a pH of 7.0 to 12.0 to form the anodized film.

[0016] Effects of the Invention

[0017] An anodic oxide film having the amorphous layer and the crystalline layer exists on the surface of the aluminum component. The amorphous layer is composed of relatively dense amorphous aluminum oxide, and thus can impart excellent insulation and corrosion resistance to the aluminum component. In addition, the crystalline layer is composed of relatively hard crystalline aluminum oxide, and thus can impart excellent wear resistance to the aluminum component.

[0018] Thus, the anodic oxide film has both the excellent insulation and corrosion resistance of the barrier type anodic oxide film and the excellent wear resistance of the plasma electrolytic oxide film. Therefore, the aluminum part has excellent insulation, corrosion resistance and wear resistance.

[0019] In addition, in the method for manufacturing the aluminum component, the base material is subjected to anodizing treatment in the specific electrolyte. By using the specific electrolyte as the electrolyte, the amorphous layer can be formed in the initial stage of the anodizing treatment. In addition, if the anodizing treatment is performed, the thickness of the amorphous material becomes thicker to a certain extent, and insulation breakdown occurs on the surface of the amorphous layer, and discharge accompanied by light emission is easily generated. Thus, the crystalline layer can be formed on the amorphous layer.

[0020] Therefore, according to the method for manufacturing an aluminum component, the anodic oxide film can be formed on the base material by a simple method.

[0021] As described above, according to the above aspect, it is possible to provide an aluminum component having an anodized film excellent in insulation, corrosion resistance, and wear resistance, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a cross-sectional view of an aluminum component in the embodiment.

[0023] Figure 2 This is an electron microscope image of a fracture surface of the anodized film of the test material B in the example.

[0024] Figure 3 This is an X-ray diffraction pattern of the test material B in the example.

[0025] Figure 4 This is an electron microscope image of the surface of the anodized film of the test material B in the example.

[0026] Figure 5 This is a diagram for explaining the method of measuring the maximum width of a pore. DETAILED DESCRIPTION

[0027] (Aluminum parts)

[0028] The aluminum component comprises a base material and an anodic oxide coating formed on the surface of the base material. The shape of the aluminum component is not particularly limited and can be set to an appropriate shape according to the purpose of the aluminum component. In addition, the anodic oxide coating can be provided on the entire surface of the base material or on a part of the base material surface.

[0029] The material of the base material of the aluminum part is not particularly limited as long as it is aluminum or an aluminum alloy. For example, as the material of the base material, high-purity aluminum, JIS A1000 series aluminum, A2000 series alloy, A3000 series alloy, A4000 series alloy, A5000 series alloy, A6000 series alloy, A7000 series alloy, A8000 series alloy, etc. can be used.

[0030] For example, when the material of the base material is an aluminum alloy with relatively high strength such as A5000 series alloy or A6000 series alloy, the strength of the aluminum part can be improved. Therefore, the aluminum part having a base material including A5000 series alloy or A6000 series alloy is suitable for applications requiring high strength such as automotive materials and structural materials.

[0031] In addition, for example, when the material of the base material is A1000 aluminum or A3000 alloy, the coloring of the anodized film can be suppressed, and the color tone of the aluminum part can be made closer to white. Such an aluminum part can be used for purposes requiring a white appearance. In addition, the closer the color tone of the aluminum part is to white, the easier it is to color the surface of the aluminum part to a desired color. Therefore, an aluminum part having a base material including A1000 aluminum or A3000 alloy is suitable for use in applications requiring design, such as exterior materials, housings of electronic devices, etc.

[0032] An anodic oxide film is formed on a base material. The anodic oxide film includes an amorphous layer formed on the base material and a crystalline layer formed on the amorphous layer.

[0033] The amorphous layer contains amorphous aluminum oxide. As mentioned above, the amorphous layer is relatively dense, so it can give the aluminum part insulation and corrosion resistance. The composition of the aluminum oxide constituting the amorphous layer is determined according to the material of the base material. That is, the amorphous layer is mainly composed of aluminum atoms and oxygen atoms. In addition to aluminum atoms and oxygen atoms, the amorphous layer may also contain alloy elements contained in the base material.

[0034] Whether an amorphous layer is formed in the anodized film can be determined based on an X-ray diffraction pattern obtained by X-ray crystal structure analysis. That is, when a broad peak with a vertex appears in the range of a diffraction angle of 20° to 40° in the X-ray diffraction pattern, it can be determined that an amorphous layer containing amorphous aluminum oxide is formed in the anodized film.

[0035] For example, the thickness of the amorphous layer can be 0.05 μm to 1.0 μm. In this case, the defects of the amorphous layer can be further reduced, and the effect of improving the insulation and corrosion resistance of the aluminum part can be more reliably exerted. From the viewpoint of more reliably obtaining the above-mentioned effects, the thickness of the amorphous layer is preferably 0.10 μm to 0.90 μm, and more preferably 0.20 μm to 0.80 μm.

[0036] The thickness of the amorphous layer is a value calculated by the following method. That is, first, a cross section of the aluminum component is observed using a scanning electron microscope or the like, thereby obtaining an electron microscope image. Ten measurement positions are randomly selected from the amorphous layer in the electron microscope image. Then, the arithmetic mean of the thickness of the amorphous layer at these measurement positions is taken as the thickness of the amorphous layer.

[0037] A crystalline layer containing crystalline aluminum oxide is stacked on the amorphous layer. As described above, the crystalline layer containing crystalline aluminum oxide is relatively hard, so it can impart wear resistance to the aluminum part. The crystalline layer is composed of crystalline aluminum oxides such as α-Al2O3 or γ-Al2O3. More specifically, the crystalline layer can be composed of α-Al2O3 or γ-Al2O3. In addition, the crystalline layer can also be composed of α-Al2O3 and γ-Al2O3. Furthermore, in addition to these aluminum oxides, the crystalline layer can also contain alloy elements contained in the base material.

[0038] Whether a crystal layer is formed in the anodized film can be determined based on an X-ray diffraction pattern obtained by X-ray crystal structure analysis. That is, in the X-ray diffraction pattern, when a diffraction peak from a crystalline aluminum oxide such as α-Al2O3 or γ-Al2O3 appears, it can be determined that a crystal layer is formed in the anodized film.

[0039] For example, the thickness of the crystal layer may be 1.0 μm or more. In this case, making the thickness of the crystal layer thick enough can more reliably exert the effect of improving wear resistance. From the viewpoint of more reliably obtaining the above-mentioned effect, the thickness of the crystal layer is preferably 2.0 μm or more, and more preferably 3.0 μm or more.

[0040] In addition, the thickness of the crystal layer is preferably 5.0 μm to 15.0 μm, more preferably 6.0 μm to 14.0 μm, and even more preferably 7.0 μm to 13.0 μm. In this case, the color tone of the aluminum part can be made closer to white. As a result, the design of the aluminum part can be further improved.

[0041] The method for measuring the thickness of the crystal layer is the same as the method for measuring the thickness of the amorphous layer. That is, first, a cross section of the aluminum component is observed using a scanning electron microscope, etc., thereby obtaining an electron microscope image. Ten measurement positions are randomly selected from the crystal layer in the electron microscope image. Then, the arithmetic mean of the thickness of the crystal layer at these measurement positions is used as the thickness of the crystal layer.

[0042] The crystal layer may have a plurality of pores opening on the surface of the aluminum component. In this case, the external light incident on the anodized film can be fully scattered in the crystal layer, so that the transparency of the anodized film is further reduced. In addition, by reducing the transparency of the anodized film, the color tone of the base material as the base can be effectively shielded. As a result, the color tone of the aluminum component can be made closer to white, further improving the design.

[0043] From the viewpoint of more reliably exerting the above-mentioned effects, the crystal layer preferably has pores having an average diameter of 1 μm or more and 20 μm or less.

[0044] The average diameter of the pores present in the crystal layer is a value calculated by the following method. That is, first, the surface of the crystal layer is observed using a scanning electron microscope or the like, thereby obtaining an electron microscope image. In the electron microscope image, 10 pores of the measurement target are randomly selected. Next, the maximum width of the pore of the measurement target, that is, the value of the maximum width among the values ​​obtained by measuring the width of the pore from various directions, is determined. The arithmetic mean of the maximum widths of the 10 pores determined in this way is taken as the average diameter of the pores.

[0045] The arithmetic mean roughness Ra of the surface of the anodized coating is preferably not less than 0.5 μm and not more than 1.5 μm. In this case, the external light incident on the anodized coating can be fully scattered on its surface, further reducing the transparency of the anodized coating. Moreover, by reducing the transparency of the anodized coating, the color tone of the base material serving as the substrate can be effectively shielded. As a result, the color tone of the aluminum component can be made closer to white, further improving the designability. It should be noted that the arithmetic mean roughness Ra of the surface of the anodized coating is a value measured by a method based on JIS B0601:2013.

[0046] The L* value in the CIE 1976 L*a*b* color space obtained by measuring the color tone of the surface of the anodized film in the aluminum part is preferably 70.0 or more. The L* value in the CIE 1976 L*a*b* color space is a value from 0 to 100, and a larger value means a higher lightness of the color tone.

[0047] By setting the L* value of the surface of the aluminum component having the specific structure to the specific range, the color tone of the aluminum component surface can be made closer to white. As described above, the aluminum component with a surface color tone close to white can be suitably used for applications requiring a white appearance.

[0048] Furthermore, for example, when coloring the surface of a white aluminum member by painting or the like, the color tone after coloring is less likely to be affected by the color tone of the base material, and a desired color can be realized more easily.

[0049] Thus, the aluminum parts having L* values ​​in the specific range can easily achieve the desired color tone, and thus have excellent design properties. From the viewpoint of further improving the design properties of the aluminum parts, the L* value in the CIE 1976 L*a*b* color space is preferably 75 or more, and more preferably 80 or more. It should be noted that from the viewpoint of further improving the design properties of the aluminum parts, the closer the L* value is to 100, which is the upper limit, the more preferable.

[0050] (Manufacturing method of aluminum parts)

[0051] The method for manufacturing an aluminum component includes a step of performing an anodic oxidation treatment on a base material in an electrolyte containing boron atoms and having a pH of 7.0 or more and 12.0 or less. When the base material containing aluminum or an aluminum alloy is anodized using the specific electrolyte, an amorphous layer containing amorphous aluminum oxide is formed on the surface of the base material in the initial stage of the anodization treatment.

[0052] If anodizing is performed, the thickness of the amorphous layer increases, and the electrical insulation of the amorphous layer increases accordingly. Moreover, the electrical insulation of the amorphous layer increases, and it is difficult for the anodic reaction to occur on the surface of the base material, so that small and irregular discharges called micro-arcs are intermittently generated on the surface of the amorphous layer. Through the micro-arcs, the surface of the amorphous layer repeatedly melts and solidifies, thereby forming a crystalline layer on the surface of the amorphous layer.

[0053] As described above, by performing anodizing treatment using the specific electrolyte solution, it is possible to easily form an anodic oxide film including an amorphous layer stacked on a base material and a crystalline layer stacked on the amorphous layer.

[0054] In the method for manufacturing the aluminum part, the base material may be subjected to pretreatment such as degreasing treatment and grinding treatment as required before the base material is subjected to anodizing treatment. As the degreasing treatment, for example, an alkali degreasing treatment using an alkali cleaning solution may be performed. By performing the degreasing treatment, the glossiness of the aluminum part obtained after the anodizing treatment can be reduced, and a matte aluminum part can be easily obtained.

[0055] In addition, as the polishing treatment, for example, chemical polishing, mechanical polishing, electrolytic polishing, etc. can be performed. By performing the polishing treatment, the glossiness of the aluminum part obtained after the anodizing treatment can be increased, and a glossy aluminum part can be easily obtained. From the viewpoint of further improving the glossiness of the aluminum part, it is preferred to perform electrolytic polishing on the base material.

[0056] As the electrolyte used for the anodizing treatment, a liquid containing boron atoms and having a pH of 7.0 or more and 12.0 or less can be used. As the electrolyte, for example, an aqueous solution of one or more electrolytes selected from the group consisting of boric acid and borates can be used. Specifically, as the electrolyte used in the electrolyte, salts of boric acid and ammonia such as ammonium tetraborate and ammonium pentaborate, salts of boric acid and alkali metal elements such as sodium tetraborate, etc. can be cited.

[0057] From the viewpoint of more easily forming an anodic oxide film having the above-mentioned specific structure, the electrolytic solution is preferably an aqueous solution of an electrolyte containing ammonium tetraborate.

[0058] About the concentration of the electrolyte, for example, it can be appropriately set from the range of 0.1mol / L or more and 1.0mol / L or less. The concentration of the electrolyte in the anodizing treatment is preferably 0.2mol / L or more and 0.9mol / L or less. In this case, the growth of the anodic oxide film in the anodizing treatment can be further promoted. As a result, the thickness of the anodic oxide film can be thickened more easily.

[0059] The temperature of the electrolyte in the anodizing treatment can be appropriately set, for example, from a range of 283 K to 343 K. The temperature of the electrolyte in the anodizing treatment is preferably 303 K to 343 K. In this case, the concentration of the electrolyte can be appropriately increased to further promote the growth of the anodized film in the anodizing treatment. As a result, the thickness of the anodized film can be made thicker more easily.

[0060] In the anodizing treatment, preferably 10A / m 2 Above 200A / m 2 The constant current electrolysis was performed at the following current density. By performing the anodizing treatment under this current condition, the growth of the anodized film during the anodizing treatment can be further promoted, and the anodized film can be grown more uniformly.

[0061] Regarding the treatment time in the anodizing treatment, for example, it can be set to more than 5 minutes. By making the treatment time in the anodizing treatment more than 5 minutes, it is possible to more easily form an anodized film stacked with a crystal layer on the amorphous layer. In addition, the longer the treatment time in the anodizing treatment, the thicker the thickness of the crystal layer will be, which can further improve the wear resistance of the aluminum part. From this viewpoint, the treatment time in the anodizing treatment is preferably more than 10 minutes, more preferably more than 20 minutes, and more preferably more than 30 minutes.

[0062] Example

[0063] Reference Figure 1 to Figure 5 The embodiments of the aluminum component and the method for manufacturing the same are described below. Figure 1 As shown, the aluminum component 1 of this example has a base material 2 including aluminum or an aluminum alloy and an anodic oxide film 3 formed on the surface of the base material 2. The anodic oxide film 3 has an amorphous layer 31 including amorphous aluminum oxide and formed on the base material 2 and a crystalline layer 32 including crystalline aluminum oxide and formed on the amorphous layer 31.

[0064] The aluminum component 1 of this example can be manufactured by the following method. First, a base material 2 containing high-purity aluminum with an Al purity of 99.99 mass % is prepared. The base material 2 is a plate having a square shape with a side of 20 mm. The surface of the base material 2 is ultrasonically cleaned with ethanol to perform a degreasing treatment, and then electrolytic polishing is performed.

[0065] By subjecting one surface of the pretreated base material 2 to anodizing treatment in an electrolyte solution containing boron atoms and having a pH of 7.0 to 12.0, the anodic oxide film 3 can be formed on the surface of the base material 2 .

[0066] In the anodizing treatment, for example, the electrolyte and treatment conditions shown in Table 1 can be used. Hereinafter, the more detailed structure of the aluminum component 1 will be described using the test materials A to K shown in Table 1 as examples. It should be noted that the test materials L to N shown in Table 1 are test materials for comparison with the test materials A to K. Except for changing the electrolyte and treatment conditions as shown in Table 1, the test materials L to N can be produced by the same method as the test materials A to K.

[0067] ·Structure of anodized coating

[0068] The structure of the anodic oxide film can be evaluated by combining cross-sectional observation using a field emission scanning electron microscope (FE-SEM) and identification of constituent materials using an X-ray diffraction device.

[0069] When performing cross-sectional observation, first, V-bend the test materials A to N so that the surface subjected to anodizing treatment is on the outside to fracture the anodized film. By observing the fracture surface of the anodized film using FE-SEM, the laminated structure of the anodized film can be evaluated. In the results of the cross-sectional observation, when the anodized film is composed of a single layer, it is recorded as "single layer" in the "laminated structure" column of Table 2; when the anodized film is a two-layer structure, it is recorded as "two layers" in this column. In addition, when the anodized film is not formed, it is recorded as "-" in this column.

[0070] In addition, when the constituent material is identified, an X-ray diffraction device (RINT2500 manufactured by Rigaku Co., Ltd.) is used to irradiate the anodic oxide film of test material A to test material N with X-rays to obtain an X-ray diffraction pattern. Then, by comparing the diffraction peaks appearing in the X-ray diffraction pattern with the diffraction patterns of known substances, it is possible to identify the substance corresponding to the diffraction peaks appearing in the X-ray diffraction pattern. In addition, in the X-ray diffraction pattern, when a broad peak with a vertex appears within a range of a diffraction angle of 20° to 40°, it can be judged that an amorphous substance is contained in the anodic oxide film.

[0071] The column "Constituent substances" in Table 2 shows substances contained in test materials A to N.

[0072] As shown in Table 2, the anodic oxide films 3 of the test materials A to K all have a two-layer structure. Figure 2 As shown in the example of test material B in FIG. 1 , the anodic oxide film 3 of test materials A to K includes: a layer formed on the base material 2 and having a relatively uniform thickness and few defects; and a layer formed on the layer and having pores, discharge marks, melting marks, etc.

[0073] In addition, as an example, Figure 3 The X-ray diffraction pattern of the test material B is shown in FIG. Figure 3 The vertical axis is the diffraction intensity, and the horizontal axis is the diffraction angle 2θ (°). Although not shown in the figure, the X-ray diffraction patterns of test material A and test materials C to test material K are the same as that of test material B. As shown in Table 2, based on these results, it can be seen that the anodized film 3 of test materials A to test material K is composed of α-Al2O3 and γ-Al2O3 as crystalline aluminum oxides and amorphous aluminum oxides.

[0074] On the other hand, in the test material L having a shorter treatment time in the anodizing treatment than the test materials A to K, a single-layer anodized film containing amorphous aluminum oxide was formed as shown in Table 2. From the comparison between the test materials A to K and the test material L, it can be seen that the layer formed on the base material 2 in the test materials A to K is an amorphous layer 31 containing amorphous aluminum oxide, and a crystalline layer 32 is formed on the amorphous layer 31.

[0075] The electrolyte in the test material M is a sodium hydroxide aqueous solution, so the dissolution rate of the anodic oxide film and the base material is faster than the growth rate of the anodic oxide film during the anodic oxidation treatment. Therefore, it is difficult to form an anodic oxide film on the surface of the test material M.

[0076] The electrolyte in the test material N was a sulfuric acid aqueous solution, so no dielectric breakdown occurred during the anodizing treatment. Therefore, a single-layer anodized film containing amorphous aluminum oxide and having pores was formed on the surface of the test material N.

[0077] Surface structure of the crystal layer

[0078] By observing the surfaces of the test materials A to K using FE-SEM, the surface structure of the crystal layer 32 can be evaluated. Figure 4 , an electron microscope image of the surface of the test material B is shown as an example. Thus, a plurality of pores 321 exist on the surface of the crystal layer 32 .

[0079] The average diameter of the pores 321 present in the crystal layer 32 is calculated as follows. First, 10 pores 321 to be measured are randomly selected from the pores 321 present in the electron microscope image. Figure 5 As shown in an example, the width W of the pore 321 of the measurement target is measured from various directions. Then, the maximum value of the width W of the pore 321 measured from various directions is taken as the maximum width W of the pore max The maximum width W of the ten fine holes 321 thus obtained is maxThe arithmetic mean of is taken as the average diameter of the pores 321.

[0080] The average diameters of the pores 321 of the test materials A to K are the values ​​shown in Table 2. It should be noted that, for the test materials L and M that do not have the crystal layer 32, since there are no pores, the symbol "-" is recorded in the "Average diameter of pores" column in Table 2. The average diameter of the pores of the test material N can be calculated by the same method as that of the test materials A to K. The average diameter of the pores of the test material N is the value shown in Table 2.

[0081] As shown in Table 2, the average pore diameter of the test materials A to K was 1 μm or more and 20 μm or less.

[0082] Evaluation of arithmetic mean roughness Ra

[0083] The arithmetic mean roughness Ra of the surface of the anodized film can be evaluated by the method according to JIS B0601:2013. Specifically, first, a laser microscope ("OLS-3000" manufactured by Olympus Corporation) is used to observe the anodized film at a magnification of 50 times to obtain a three-dimensional image containing the height information of the surface of the anodized film. In the three-dimensional image thus obtained, the arithmetic mean roughness Ra of three randomly selected places is calculated. Then, the arithmetic mean of the arithmetic mean roughness Ra of these three places is taken as the arithmetic mean roughness Ra of the surface of the anodized film. The arithmetic mean roughness Ra of the surface of the anodized film of test materials A to test materials K and test material N is the value shown in Table 2. It should be noted that, for test materials L and test material M, since they do not have a crystal layer 32, it is not necessary to measure the arithmetic mean roughness Ra. Therefore, the symbol "-" is recorded in the "arithmetic mean roughness Ra" column of these test materials.

[0084] Next, a method for evaluating the characteristics of the aluminum member 1 will be described.

[0085] Appearance characteristics

[0086] The appearance characteristics of the aluminum member 1 can be evaluated based on the uniformity of the appearance of the anodized film 3 observed visually and under SEM. The meanings of the symbols described in the "Appearance Characteristics" column of Table 2 are as follows.

[0087] A: The appearance of the anodized film is uniform in both visual and SEM observations.

[0088] B: The appearance of the anodized film is uniform when visually observed, but in SEM observation, there are a mixture of parts with discharge marks and parts without discharge marks.

[0089] C: The appearance of the anodic oxide film is uneven when visually observed, but there are parts where discharge marks are formed when observed under SEM.

[0090] D: The appearance of the anodized film is uneven when visually observed, and there is no portion where discharge marks are formed when observed under SEM.

[0091] Design

[0092] The design of the aluminum component 1 can be evaluated based on the color tone of the surface having the anodized coating 3. The "Design" column of Table 2 shows the L* values ​​of the CIE (International Commission on Illumination) 1976 L*a*b* color space of test materials A to test materials K and test material N. It should be noted that in the determination of the L* value, a spectrophotometer in accordance with JIS Z8781-4:2013 (for example, a colorimeter "CC-iS" manufactured by Suga Testing Instruments Co., Ltd.) can be used. It should be noted that test material L does not have a crystalline layer, so the symbol "-" is recorded in the "Design" column. In addition, test material M does not have an anodized coating, so the symbol "-" is recorded in the "Design" column.

[0093] [Table 1]

[0094]

[0095] [Table 2]

[0096]

[0097] As shown in Table 1, the anodic oxide coating 3 of the test materials A to K has a two-layer structure in which a crystalline layer 32 is stacked on an amorphous layer 31. Therefore, as shown in Table 2, these test materials can be expected to have both excellent insulation and corrosion resistance from the amorphous layer 31 and excellent wear resistance from the crystalline layer 32.

[0098] The average diameter of the pores 321 in the crystal layer 32 of the test materials A to K and the arithmetic mean roughness Ra of the test materials A to K were within the specific ranges. Therefore, the appearance of the test materials A to K was white and opaque, and had excellent design properties.

[0099] The anodizing treatment time of the test material L was shorter than that of the test materials A to K, so that during the anodizing treatment, dielectric breakdown did not occur on the surface of the amorphous layer 31 . Therefore, it was difficult for a crystalline layer to form on the amorphous layer 31 of the test material L.

[0100] The electrolyte in the test material M is a sodium hydroxide aqueous solution, so the dissolution rate of the anodic oxide film and the base material is faster than the growth rate of the anodic oxide film during the anodic oxidation treatment. Therefore, it is difficult to form an anodic oxide film on the surface of the test material M. Therefore, it is estimated that the test material M is inferior to the test materials A to K in terms of insulation, corrosion resistance, and wear resistance.

[0101] The electrolyte in the test material N is a sulfuric acid aqueous solution, so insulation breakdown does not occur during the anodizing treatment. Therefore, it is difficult to form a crystal layer on the surface of the test material N. Therefore, it is estimated that the wear resistance of the test material N is inferior to that of the test materials A to K. In addition, the transparency of the anodized film formed on the surface of the test material N is high, so the appearance of the test material N is likely to be a color tone close to the color tone of the base material.

[0102] As described above, the specific aspects of the aluminum component and the method for manufacturing the same are described based on the embodiments, but the aspects of the aluminum component and the method for manufacturing the same of the present invention are not limited to the aspects in the above-mentioned embodiments, and the structure can be appropriately changed within the scope of the gist of the present invention.

Claims

1. A method for manufacturing an aluminum component, The aluminum component includes a base material including aluminum or an aluminum alloy and an anodic oxide film formed on a surface of the base material. The anodic oxide film includes an amorphous layer formed on the base material and including amorphous aluminum oxide, and a crystalline layer formed on the amorphous layer and including crystalline aluminum oxide. In the manufacturing method, the base material is subjected to anodizing treatment in an electrolyte solution containing boron atoms and having a pH of 7.0 or more and 12.0 or less, thereby forming the anodized film. The electrolyte is an aqueous solution of one or more electrolytes selected from the group consisting of boric acid and borates. In the anodizing treatment, the temperature of the electrolyte is set to 283K or higher and 343K or lower, and the electrolyte is charged at 10A / m 2 Above and 200A / m 2 The following current density was used for constant current electrolysis: The treatment time in the anodizing treatment is 30 minutes to 60 minutes.

2. The method for manufacturing an aluminum component according to claim 1, wherein: The crystal layer has pores having an average diameter of 1 μm or more and 20 μm or less.

3. The method for producing an aluminum component according to claim 1 or 2, wherein: The surface of the anodized film has an arithmetic mean roughness Ra of 0.5 μm or more and 1.5 μm or less.

4. The method for manufacturing an aluminum component according to claim 1 or 2, wherein: The L* value of the CIE 1976 L*a*b* color space obtained by measuring the color tone of the surface of the aluminum member having the anodized film is 70.0 or more.

5. The method for producing an aluminum component according to claim 1 or 2, wherein: The electrolyte is an aqueous solution of ammonium tetraborate.

Citation Information

Patent Citations

  • Method for forming anodized alumina film

    JP1998107027A

  • Method for forming ceramic film on aluminum substrate surface

    JP2003171794A

  • Aluminum alloy member, and method for forming surface protective film of aluminum alloy

    JP2015025184A

  • Heat exchanger and manufacturing method of the same

    US20100282455A1